Non-invasive respiratory support in patients with severe community-acquired pneumonia - S. V. Korotchenko; D. I. Korabelnikov (Фармакоэкономика, 2023)
Acute respiratory failure (ARF) is the leading cause of death in hospitalized patients with severe forms of COVID-19. At the beginning of COVID-19 pandemic the starting respiratory protocol suggested early use of intubation and artificial lung ventilation (ALV) in patients with severe pneumonia complicated by ARF. However, after the analysis of the published studies it was noted that the pathophysiology of the development of ARF in COVID-19 had features that determine the atypical clinical pattern – “silent hypoxemia”. This leads to the late onset of respiratory support (RS) and, as a result, to the lower effectiveness of non-invasive RS methods. This article discusses the creation of an algorithm for the early use of various non-invasive RS methods in patients with COVID-19 complicated by ARF, that will decrease the frequency of hospitalization to the Intensive care units, tracheal intubation and ALV, reduce the duration of treatment and improve prognosis.